Orbital Prosthesis Fabrication - Shreya Gupta; Sachin Gupta (Delhi Journal of Ophthalmology)
Unacceptable cosmetic disfigurement occurs following destructive procedures or accident. An orbital prosthesis serves as a major morale booster in these patients by combating the physical and emotional trauma. This article describes a simplified technique for fabrication of silicone orbital prosthesis.